2016
DOI: 10.1183/23120541.00037-2016
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity and carotid artery disease in COPD

Abstract: In view of their common chronic inflammatory process, we sought to determine the linkage between peripheral artery disease and chronic obstructive pulmonary disease (COPD).107 COPD patients (mean±sd age 64.6±10.4 years, 52.2% male) and 22 control smokers without previously diagnosed peripheral artery disease underwent standardised angiological examination for lower extremity artery disease (LEAD) and carotid artery disease.LEAD was significantly more prevalent in COPD patients than in controls (80.4% versus 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…The same, i.e. a high frequency of LEAD in COPD patients (80.4%), was also demonstrated by Pizzaro et al, [18]. On the other side, Watz et al demonstrated a lower frequency of LEAD in COPD patients (25.3%) [35].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The same, i.e. a high frequency of LEAD in COPD patients (80.4%), was also demonstrated by Pizzaro et al, [18]. On the other side, Watz et al demonstrated a lower frequency of LEAD in COPD patients (25.3%) [35].…”
Section: Discussionsupporting
confidence: 65%
“…Vascular changes are one of the cardiovascular complications of COPD, probably due to the chronic, low-grade, systemic inflammation that leads to atherosclerosis in carotid and other arteries [29]. The inflammatory cascade that initially arises from exposure to noxious substances, mainly tobacco smoke, accelerates atherogenesis at all stages by formation, destabilisation and rupture of plaque as well as by platelet activation and clotting that lead to atheroma formation and atherothrombosis [18]. Nevertheless, the association between COPD and vascular comorbidities, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent occurrence of stenosis, severe lesions, and markedly calcified coronary plaques, especially in the GOLD III group (even with the small sample), was another finding of this study and reinforces the conclusion that the inflammatory processes of COPD do not participate only in the formation of atherosclerotic plaques but also in their progression. 30 32 …”
Section: Discussionmentioning
confidence: 99%
“…Smoking and diabetes are the two main risk factors for peripheral arterial disease. Therefore, it is not surprising that a 22% of our participants had peripheral arterial disease, presenting an ABI < 0.9, an association with COPD that has been reported as between 8.5% [41] and 41% [42]; nevertheless, we found no differences between the exacerbator and non-exacerbator groups.…”
Section: Tablementioning
confidence: 42%